Pengaruh Model Pembelajaran STAD terhadap Kemampuan Berpikir Kritis Siswa Multietnis di SMP Negeri Kota Ternate - Muhammad Hidayat; Gusti Dodego (Jurnal Ilmiah Wahana Pendidikan, 2021)
This research was conducted with the following objectives: (1) To find out whether there is an effect of the Problem Beased Learning (PBL) learning model on learning motivation in seventh grade students of SMP Peduli Bangsa Wooi, East Obi District, South Halmahera Regency. (2) To determine the effect of the Problem Beased Learning (PBL) learning model on the mastery of the concepts of seventh grade students of SMP Peduli Bangsa Wooi, East Obi District, South Halmahera. March to June 2021. The population in this study were all students of class VII, totaling 40 people who were divided into two study groups, namely the experimental study group and the control group. The test method was carried out through pretest and posttest. The results showed that it was concluded that (1) the Problem Beased Learning (PBL) learning model could increase student motivation at Peduli Bangsa Wooi Junior High School, East Obi District, South Halmahera Regency. the average value of the Problem Beased Learning (PBL) learning model was 93.50 (very good) increased to 96.00 (very good) while the control class (lecture) reached an average value of 81.00 (very good) increased to 91, 00 (very good). (2) Problem Based Learning (PBL) learning model has an effect on students' mastery of concepts at SMP Peduli Bangsa Wooi, East Obi District, South Halmahera Regency, this can be seen in the ANOVA test with a significant value of 0.00≤0.05 or p≤0.05 .